SOSIALISASI SISTEM AGROFORESTRI UNTUK MENINGKATKAN KESUBURAN TANAH DAN PENDAPATAN MASYARAKAT DESA WAAI KECAMATAN SALAHUTU MALUKU TENGAH - Irwanto, Irwanto; Sahupala, Andjela; Wattimena, Cornelia Marietje Aneke; Lelloltery, Henderina; Talaohu, Moda; Iskar, Iskar; Seipalla, Billy; Louhenapessy, Fredy Hendry (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Waai Village in Salahutu District, Central Maluku, is an area with diverse topography which poses challenges for agriculture and fisheries, such as soil erosion and landslides. To overcome this problem, an agroforestry system is implemented as a sustainable land management solution. This research aims to socialize and evaluate the implementation of agroforestry in Waai Village, with a focus on reducing erosion, increasing soil fertility, and diversifying community income. The implementation method involves lectures, presentations, practical training, and distribution of plant seeds. This activity was carried out on 11-12 August 2023 by the Forestry Study Program, Faculty of Agriculture, Pattimura University with the participation of the local community. An initial survey was conducted to understand soil conditions, slope and community knowledge about agroforestry. Lectures and presentations provide basic information and techniques for implementing agroforestry, while practical training introduces vegetative methods in growing agroforestry crops. The results of the activity show that the community has a high interest in implementing agroforestry, with a significant increase in understanding and skills. The evaluation shows a good level of satisfaction and strong commitment from the community to develop agroforestry systems. The implementation of agroforestry is expected to reduce erosion, increase soil fertility and diversify people's income through high-value products such as wood and fruit. Agroforestry offers an effective solution to overcome the problem of erosion and landslides in Waai Village, while improving the economic welfare and food security of the community.